2010
DOI: 10.1523/jneurosci.5966-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Rett Syndrome Microglia Damage Dendrites and Synapses by the Elevated Release of Glutamate

Abstract: MECP2, an X-linked gene encoding the epigenetic factor methyl-CpG-binding protein-2, is mutated in Rett syndrome (RTT) and aberrantly expressed in autism. Most children affected by RTT are heterozygous Mecp2−/+ females whose brain function is impaired postnatally due to MeCP2 deficiency. Recent studies suggest a role of glia in causing neuronal dysfunction via a non-cell-autonomous effect in RTT. Here we report a potent neurotoxic activity in the conditioned medium (CM) obtained from Mecp2-null microglia. Hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
318
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(335 citation statements)
references
References 77 publications
6
318
1
2
Order By: Relevance
“…Recent studies revealed that MeCP2 is also expressed in glia-albeit at lower levels than neurons-and that glia lacking MeCP2 fail to support dendritic morphology of either wild-type or Mecp2-null neurons (Ballas et al 2009;Maezawa et al 2009;Kifayathullah et al 2010;Maezawa and Jin 2010). These studies raised the possibility that some noncell-autonomous effects from glia contribute to RTT pathogenesis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Recent studies revealed that MeCP2 is also expressed in glia-albeit at lower levels than neurons-and that glia lacking MeCP2 fail to support dendritic morphology of either wild-type or Mecp2-null neurons (Ballas et al 2009;Maezawa et al 2009;Kifayathullah et al 2010;Maezawa and Jin 2010). These studies raised the possibility that some noncell-autonomous effects from glia contribute to RTT pathogenesis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…As neuronal stem cells differentiate into neurons, MeCP2 expression gradually increases. Recently, glial cells were also found to express MeCP2 and to play an important role in pathogenesis of RTT (12)(13)(14).…”
mentioning
confidence: 99%
“…Microglia may also influence the onset and progression of RTT. Elevated levels of glutamate, released from microglia, may cause abnormal stunted dendritic morphology, microtubule disruption, and damage to postsynaptic glutamatergic components making microglial glutamate synthesis or release a potential therapeutic target for RTT (48,49). Since most cases of RTT are caused by mutations in the MECP2 gene, it is assumed that convulsions are based on genetic mechanisms, however, the balance of excitation and inhibition is also believed to play a critical role in the progression of the disease during early development.…”
Section: Brain Structure and Function Of Rtt Patientsmentioning
confidence: 99%
“…Archer stated that the generation of isogenic control and mutant RTT-hiPSCs allow the mixing and matching of WT and mutant expressing cells in different proportions which provide an opportunity to study the effects of XCI skewing as observed in RTT patients (106). Furthermore, it will also allow the mixing and matching of different cell types such as neurons and glia to study the non-cell autonomous effects of non-neuronal cell types in RTT has become apparent in the recent RTT literature (48,(109)(110)(111). In addition, X-chromosome contains a high density of genes important for brain development and reproduction, and ID is approximately three times more often related to genes on the X versus autosomes (112).…”
Section: In Rttmentioning
confidence: 99%